2018
DOI: 10.1016/j.ijnss.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an educational intervention in caregiving outcomes in Jordanian caregivers of patients receiving hemodialysis: A single group pre-and-post test

Abstract: Objectives Chronic renal failure affects the physiological, psychological, functional ability, and independent status of the patient, which might result in a burden to the family members caring for them. The objective of the study was to identify caregivers' level of burden and establish the impact of educational intervention programs on caregiving outcomes. Methods This was a one-group pre-test post-test study conducted between April and August 2017 on family caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 15 publications
(21 reference statements)
0
28
1
1
Order By: Relevance
“…Jordan has no national census on family caregivers’ numbers and attributes, nor does it have a national policy for supporting their needs. In addition, studies of family caregivers of Jordanian patients indicated that caregivers were often not acknowledged by formal health care providers and were not prepared to handle caregiving tasks (Alnazly, 2018; Salehitali et al, 2018). The lack of formal attention to family caregivers contradicts what Jordanian society expects from family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Jordan has no national census on family caregivers’ numbers and attributes, nor does it have a national policy for supporting their needs. In addition, studies of family caregivers of Jordanian patients indicated that caregivers were often not acknowledged by formal health care providers and were not prepared to handle caregiving tasks (Alnazly, 2018; Salehitali et al, 2018). The lack of formal attention to family caregivers contradicts what Jordanian society expects from family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Whereby healthcare workers from RMNH at the sampled health facilities were assessed on their training needs at baseline. The choice of this design is because it has been widely used in healthcare settings previously (Agrawal et al, 2021;Alnazly, 2018;Neil-Sztramko, Coletta, Dobbins, & Marr, 2020). Tailored training based on the identi ed and prioritized needs was implemented through a series of short courses.…”
Section: Methodsmentioning
confidence: 99%
“…Although CPD courses delivered has been found to improve the competencies of healthcare workers (Alnazly, 2018;Cavicchiolo et al, 2018;Lutenbacher, Elkins, Dietrich, & Riggs, 2018). Tanzania currently has no documented formal program that respond to training needs identi ed by healthcare workers themselves.…”
mentioning
confidence: 99%
“…It also acts as a form of prevention to reduce anxiety, so the view of life becomes broader and the person is not easily stressed (Ratna, 2010). Families have an important role because they provide physical and emotional assistance to family members with physical illness, mental illness, or other conditions (Alnazly, 2018). Families are the best caregiving source for patients undergoing hemodialysis and have a fundamental role in managing and improving the quality of life of hemodialysis patients (Sajadi et al, 2017).…”
Section: Kontakt / Journal Of Nursing and Social Sciences Related To mentioning
confidence: 99%